The interactive effect between economic uncertainty and life history strategy on corrupt intentions: a life history theory approach - Sai, Xueying; Zhu, Lei (Frontiers in Psychology, 2024)
Introduction Why do some people show more corruption when facing uncertain environment? The present study aimed to give a plausible answer from an evolutionary perspective: this might be rooted in people’s different life history strategies (slow vs. fast). Methods The present study measured the participants’ corrupt intentions by a hypothetical scenario and primed the feeling of economic environmental uncertainty by requiring the participants to read economic uncertainty (vs. neutral) materials. Results It is revealed that the participants with fast life history strategies had stronger corrupt intentions after reading materials about economic uncertainty than reading neutral materials. In addition, the desire for power mediated the interactive effect between life history strategy and economic uncertainty on corrupt intentions for fast life history strategists. Discussion This finding was discussed for its theoretical and practical implications from the perspective of life history theory.